1994
DOI: 10.1002/ajh.2830450315
|View full text |Cite
|
Sign up to set email alerts
|

IgE plasma cell leukemia successfully treated with combination VAD (vincristine, doxorubicin, dexamethasone) and MP (melphalan, prednisolone) followed by interferon‐α

Abstract: A 69-year-old woman with IgE/kappa plasma cell leukemia (PCL) was treated with a sequential combination of VAD (vincristine, doxorubicin, dexamethasone) and MP (melphalan, prednisolone) followed by interferon-alpha (IFN alpha). A complete remission was achieved for 14 months. Maintenance therapy with IFN alpha has continued for an additional 10 months. IgE PCL is extremely rare. The biological characteristics of the myeloma cells, including surface marker, adhesion molecule, karyotype, DNA analysis, and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Otherwise, recent reports have demonstrated that maintenance with INF-α significantly prolongs the remission duration in patients with multiple myeloma responding to chemotherapy [12]. This approach could also be useful in PCL, as Yamagata et al [5]have previously described, and the present patient supports.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Otherwise, recent reports have demonstrated that maintenance with INF-α significantly prolongs the remission duration in patients with multiple myeloma responding to chemotherapy [12]. This approach could also be useful in PCL, as Yamagata et al [5]have previously described, and the present patient supports.…”
Section: Discussionsupporting
confidence: 77%
“…Combination chemotherapy with the regimens used in multiple myeloma is a better approach to the treatment of PCL because drugs like dexamethasone are active against differentiated plasma cells and could achieve a great reduction in the tumor burden, while other drugs like melphalan and INF-α are more effective in reducing the clonogenic myeloma cells [4]. Unfortunately, the studies reporting the combined use of melphalan and prednisone for PCL did not show an increase either in the rate or in the duration of remissions [5]. Combination chemotherapy with three or more drugs has also been used, and occasionally longer remissions have been described.…”
Section: Discussionmentioning
confidence: 99%
“…Several IgE-MM patients have been successfully treated employing conventional regimens such as MP, VAD, or interferon-a [3,18]. As our patient was much older than 65 years and also had cardiac complications, MP therapy was selected as a first line, but it had only partial, transient effects on the clinical symptoms (edema and ascites) and the reduction in serum IgE.…”
Section: Discussionmentioning
confidence: 98%
“…Macro et al [16] demonstrated a higher incidence of PCL in IgE PCDs than that in other classes of PCDs (approximately 18% vs. 1.5-2%), although the former presents various clinical pictures as well. Including our patient described, we found 8 cases of IgE-producing PCL in the literature (6 primary and 2 possible secondary PCLs [1,5,[17][18][19][20][21]) (Table 1). Notably, 4 of 6 primary IgE PCL patients had neither osteolytic skeletal lesions nor elevation of serum calcium concentrations.…”
Section: Discussionmentioning
confidence: 92%
“…IgEproducing PCDs are considered to represent less than 0.01% of all types of multiple myeloma (MM)-related diseases [4], and thus fewer than ten patients of plasma cell leukemia (PCL) with IgE secretion have been reported [5]. Clinical and pathological features of IgE PCDs have not been sufficiently analyzed because of a small number of such patients.…”
Section: Introductionmentioning
confidence: 99%